The Influence of Negative Temperature son the Heat Conductivity Factor of Road-Building Materials - Jan Celko; Jarmila Cardosova (Communications - Scientific letters of the University of Zilina, 2001)
Appraisal of pavement from preservation against frost influence point of view is important point of its structure evaluation. The Slovak climatic conditions originate the same cycles of pavement and subgrade freezing during a winter period. This effect is dangerous from surface deformation and loss of serviceability point of view. Therefore is necessary to know the thermo-technical properties of layers’ materials for structure design. The values in nature state are measuredand evaluated only, although during freezing process the characteristics in frozen state are active. Therefore an article deals with measuring of a heat  conductivity factor of building materials during negative temperature by method of non-stationary thermal flow. The asphalt mixtures used for pavement wearing courses and some type of subgrade soils were selected for analysis.